Simulating internet auctions online: effects of learning and experience. (31st August 2005) - Noy, Avi; Rafaeli, Sheizaf
This is an empirical study of the effects of learning and experience on bidding behaviour in repeated simulated internet English and Dutch auctions. First, we introduce a simulation framework for the learning and research of behaviour in internet auctions. In this online simulation framework, human participants play against simulated bidders. Later, we describe the characteristics, abilities and limitations of this framework. In the second part of the article we report on a study, conducted using the same environment, of the effects of learning and experience on bidding behaviour in repeated English and Dutch auctions. We found evidence for a strategy change over time and compared the difference in learning between the two auction models.